A Series of Nanocomposites of Chitosan/Rectorite: Preparation, Characterization and Application for Adsorption of Cu(II), Pb(II) and Cd(II) - Li, S.Q.; Zhou, P.J.; Chen, S. (Asian Journal of Chemistry, 2013)
In this study, a series of nanocomposites of rectorite/chitosan (REC/CS) was prepared via controlling different mass ratios of chitosan to rectorite using the water phase intercalation technique. The structure of the nanocomposites was characterized. The adsorption properties of the nanocomposite toward Cu(II), Pb(II) and Cd(II) were investigated. The results showed that when rectorite:chitosan (w/w) was 3:1, the adsorption capacities was best. Besides, the variable affected factors on adsorption capacities such as pH of the solution, adsorption time, initial metal concentration were also investigated. The results demonstrated that the maximum adsorption occurred at pH 6, the adsorption time is 0.5 h and the concentration of the metal solution was 20 mg/L. By analyzing the experimental data, intra-particle diffusion was found to take part in the adsorption process, the adsorption isotherm correlated with Langmuir adsorption model.